Generasi Rabbani - Hamzah Hamzah (TASAMUH: Jurnal Studi Islam, 2020)
Da'wah should see what is needed by Muslims. Da'wah in the midst of intellectual society in the sense that the level of human resources is quite high then the da'wah must be rational especially if the mad'unya stands on a completely secular understanding. Likewise, preaching in urban areas will be different from preaching in villages that happen to be grandparents and grandmothers with weak human resources, so preaching should not rely too much on logic and philosophy. In the midst of a fairly ordinary society would certainly be appropriate if the preaching in the form of interesting stories and do not require a lot of ratio in comprehending the contents of preaching. Until now the preaching media continues to experience development, in line with increasingly rapid technology, such as the rise of the internet, television, vcd, mp3, cellular, radio, magazines, and so on, which makes it easy to convey information in a short time and wide range, so effective and efficient. This is what is now used by many scholars to be used as media propaganda; by relying on the principles of effectiveness and efficiency, where in a missionary activity must try to balance the time and energy costs incurred with the achievement of the results, even if possible time costs and a little energy can obtain maximum results